LEARNING STYLE SEBAGAI UPAYA PENINGKATAN PRESTASI BELAJAR - Zalik Nuryana (MUADDIB Jurnal Kependidikan dan Keislaman, 2017)
Learning is the basic human need to know something, whether packed formally or not. There is not one method that is appropriate and certainly appropriate with all students. Students have their own learning styles between one another can’t be equated. Real memorable learning comes from the will of the heart, not coercion. The uniqueness of each individual is what makes the variety of learning styles should be understood so that each student can overcome difficulties learning. In the implementation of learning many teachers doesn’t understand the learning style, so as to force students to always pay attention to the speech and explanation of teachers. The learning process will be effective if the method of learning  used can accommodate students. Research on the most appropriate teaching methods turns out to be a failure, because each teaching method depends on the way or style of the student in learning. This research was conducted in the school as a place of observation (field research) by using a quantitative approach. Data were collected by questionnaires, observations, interviews, and document studies which were then processed and analytically analyzed descriptively. The results of research showed that a class can not be equally aligned using and applying a single learning method only. Because in the class there are several learning styles of students. The student's learning style visually dominates the class, followed by the auditorial style, and the kinesthetic style. This research also provides advice to educators / teachers to understand the diversity of student learning styles. so that with the basic teachers are required to be more creative and innovative in applying the method of learning so that all learning styles of students can be accommodated, so that with this understanding of learning achievement can be improved.